Comparative prognosis of pediatric lymphoblastic lymphoma: insights from Chinese and international cohorts - Zhang, Luyao; Zhou, Jianwen; He, Yongyan; Chen, Tianhui; Liu, Wei (Frontiers in Oncology, 2025)
ObjectiveThe aim of this research was to characterize the clinical features and histological subtypes of pediatric lymphoblastic lymphoma (LBL) and to assess the clinical prognostic factors for 178 pediatric patients. Data from two independent cohorts were used: the China-LBL cohort and the United States Surveillance, Epidemiology, and End Results (SEER)-LBL cohort.MethodsA retrospective analysis was conducted using SEER data and a single-center cohort of pediatric patients from China. Survival analysis and prognostic factor evaluations were performed to identify patterns and discrepancies between the two cohorts. Patients diagnosed with LBL from both the China-LBL and SEER-LBL cohorts were included. Statistical analyses involved the chi-square test, Kaplan-Meier method, and multivariate Weibull regression for survival analysis.ResultsThe study identified 77 patients in the China-LBL cohort and 101 patients in the SEER cohort. In the China-LBL cohort, 60 (77.9%) were T-LBL and 17 (22.1%) were B-LBL. In the SEER-LBL cohort, 65 (64.4%) were T-LBL and 36 (35.6%) were B-LBL. The highest proportion of patients was observed in stage IV in both cohorts (China-LBL: 80.5%; SEER-LBL: 48.5%). The overall survival between B-LBL and T-LBL patients was not significantly different in either cohort (SEER: P = 0.79; China: P = 0.14). Furthermore, patients treated during 2017–2019 had significantly better overall survival compared to those treated between 2020–2023 in both the entire LBL cohort (P <.001) and the T-LBL subgroup (P = 0.003) of the China cohort. Multivariate analysis did not identify any independent prognostic factors in either the SEER or China cohort. The overall survival of LBL patients in the China cohort showed statistically significant differences between the periods of 2017–2019 and 2020-2023, across gender, age, histology, and primary site groups.ConclusionPediatric lymphoblastic lymphoma (LBL) is predominantly T-cell subtype (China: 77.9%, SEER: 64.4%) and frequently diagnosed at stage IV. Survival did not differ between B- and T-LBL, but China cohort patients treated in 2017–2019 had better outcomes than those in 2020–2023 (P<0.01), possibly linked to COVID-19 disruptions. No independent prognostic factors were identified, warranting larger studies integrating treatment details to refine risk stratification.